Peningkatan Kandungan Metabolit Sekunder Tanaman Aneka Kacang sebagai Respon Cekaman Biotik - Sulistiyo Dwi Setyorini; Eriyanto Yusnawan (Puslitbang Tanaman Pangan, 2016)
Secondary metabolites are not considered as essential compounds for plant growth. The increase of secondary metabolites produced by plants is only expressed in certain situations. These compounds are unique and different for each species. Various types of plants, including legume crops are able to produce secondary metabolites in certain situations. Plants produce secondary metabolites as a defense mechanism to stresses, both biotic and abiotic stresses. Biotic stresses that occur on plants can be caused by pests, diseases or weeds. For human, secondary metabolites can be toxic or beneficial compounds depending on the type of compound formed. Secondary metabolites have been used as a medicine, pesticide and become materials for cosmetic production. Legumes can produce secondary metabolite compounds that act as antioxidant for human, so it is necessary to improve these expression. One of the efforts is the use of elicitors. The combination of the elicitors and time of application can be used to improve the production of plant secondary metabolites.